(untitled) (International Journal of Innovative Technologies in Economy, 2025)
Accounting fraud in Indonesia remains a recurring issue faced by many companies. The fraud triangle theory explains that fraud may occur due to pressure, opportunity, and rationalization. This study aims to examine the factors that contribute to accounting fraud from the perspective of the fraud triangle. The sample comprises financial reports from 26 property companies listed on the Indonesia Stock Exchange between 2021 and 2022. Logistic regression was used as the analytical tool. The findings show that external pressure, industry conditions, and rationalization have no significant effect on fraud, while audit quality does influence accounting fraud. This study is expected to provide insights for companies to anticipate accounting fraud by implementing preventive measures within their organizations.